Cutaneous metastasis of prostate carcinoma to neck and upper chest - Nitin Abrol; Amlesh Seth; Priti Chattergee (Wolters Kluwer Medknow Publications, 2011)
Prostate adenocarcinoma is the most common urologic malignant neoplasm in men. Metastasis to skin is rarely reported and usually occurs late. The incidence and appearance of cutaneous metastasis are not well established in patients with prostate adenocarcinoma and their recognition remains poor among practicing urologists. Their clinical appearance may mimic other common dermatologic disorders. Definitive diagnosis requires a high index of suspicion. Immunohistochemical staining helps in establishing the diagnosis. We report a case of prostate adenocarcinoma presenting with widespread metastasis, including those to dermis and subcutaneous tissue of neck and upper chest.